𝒥ℋ-Operator Pairs with Application to Functional Equations Arising in Dynamic Programming. (13th February 2014) - Razani, A.; Moeini, B.
Abstract : Some common fixed point theorems for 𝒥 ℋ -operator pairs are proved. As an application, the existence and uniqueness of the common solution for systems of functional equations arising in dynamic programming are discussed. Also, an example to validate all the conditions of the main result is presented.